Jihad Nir Kekerasan dalam Penafsiran Sholeh Darat Pada Ayat-Ayat Qitāl - Nor Lutfi Fais; Ahmad Murtaza MZ; M. Saiful Mujab (QOF, 2022)
Several verses of the Qur'an, especially those discussing qitāl,, are often used as legitimacy to commit acts of violence and terror. Al-Baqarah 190-193 instructs Muslims to kill non-Muslims in the name of Allah or it is called the Holy War. Several scholars, both salaf and contemporary, have interpreted this verse with various methods and produced various ideas. In this article, the author tries to explain the Isyari exegesis method that has been used by Sholeh Darat in this verse and produces the values of Sufism and non-violence in Islam. With the isyari method, Sholeh Darat interprets the word war or qitāl,in this verse as a war within ourselves. Even though he lived during the Dutch colonial period, he did not necessarily use this verse to inflame the spirit of war but interpreted it with nonviolent values, namely self-improvement through controlling emotions, desires, and lust. This research found that war in the interpretation of Sholeh Darat focused on the spiritual, namely fighting whatever hindered the soul from reaching its God. Besides that, Sholeh Darat's response to colonialism will also be presented. He used a cultural and intellectual approach to fight colonialism rather than physical resistance. Therefore, this study concludes that the Isyari-Sufi interpretation is closely related to the values of peace and non-violence.